Effects of Masks on the Preference of Laser Treatment during the COVID-19 Pandemic in the Japanese Population - Takeshi Nomura; Hanako Otsuka; Gan Muneuchi (Journal of Plastic and Reconstructive Surgery)
Objectives: The coronavirus disease 2019 pandemic has encouraged the use of masks in Japan, and areas of the face that are covered by masks are less likely to be seen by others. This concealment may lead to a decrease in laser treatment in masked areas; however, no study has examined this change. This retrospective comparative study investigated the effects of mask use during the coronavirus disease 2019 pandemic on facial regions targeted for laser treatment among Japanese patients. Methods: We compared two groups of 103 patients who underwent facial laser treatment before and after the pandemic onset. We analyzed patient data, such as age, sex, treatment area, and preferences in masked and unmasked areas. Results: The number of patients seeking laser treatment remained unchanged during the two 3-year periods before and after the pandemic onset. However, after the onset of the pandemic, the number of patients who desired treatment only outside the masked area significantly increased. Treatment area preferences significantly shifted from the cheeks before the pandemic to the eyelids and glabella after the onset of the pandemic. Conclusions: The findings suggest that the coronavirus disease 2019 pandemic has influenced the facial areas where patients seek cosmetic enhancements, possibly due to changes in mask-wearing habits and social behaviors. Plastic and cosmetic surgeons should be aware of these changes in aesthetic preferences to provide updated and relevant treatments to their patients. Further studies are needed to better understand the impact of the pandemic on cosmetic preferences and practices.